Empleo de gráficas en el estudio del concepto de elasticidad en el sistema óseo: experiencia en un curso de mecánica en la carrera de medicina - Marín-Santamaría, Y.C.; Puentes-Ossa, A.M. (Revista Científica, 2011)
The teaching of physics in the biomedical sciences and in medicine specifically involves creating new methods that allow the student to understand the concepts, laws and scientific theories, from their training as doctors, contributing to the use of the concepts learned during his tenure professional. In that vein, with the aim of contributing to the understanding of the concept of elasticity in the study of the biomechanics of bone was designed and implemented, based ongraphs of stress and deformation of bones subjected to different types of loads, a unit Teaching for the study of Hooke's law and Young's modulus in the mechanics course in medical carrier.At the end of the implementation of the teaching unit test was applied in the context where concepts taught and evaluated students' skills in interpreting graphs, this was made from plots stress and deformation of bones, a result of investigations in patients of different ages, subjected to different types of loads (Nordin & Frankel, 2001). In thispaper we present the methodology and results of its implementation.